JOINT STRUGGLES AND COMMON AGENDAS: THE ARTICULATION POLICY OF THE NETWORK OF AFRO-LATIN AMERICAN, AFRO-CARIBBEAN AND DIASPORA WOMEN - Busquier, Lucía María (2025)
This paper aims, rstly, to reconstruct the debates and main events that were carried out by the Network of Afro-Latin American, Afro-Caribbean and Diaspora Women (RMAAD) during the years 2006 and 2019, a period that began with the III Meeting of Black Women of Latin America and the Caribbean. Characterized by a strengthening of internal structures and greater prominence of its regions. Secondly, one of its denitions and political strategies linked to the dialogues and articulation policies carried out by the RMAAD with other social movements such as the Afro- descendant collective, the feminist movement, the indigenous movement and the LGBTI or LGTB movement will be addressed. To do this, references will be mainly taken from in-depth interviews carried out with activists and representatives of the RMAAD. In turn, written documents such as conference resolutions and advocacy and evaluation plans produced by the organization itself will be considered. Both racial and gender issues were the main variables of oppression considered by the RMAAD, which facilitated alliances with indigenous women, with the Afro- descendant community and, to a lesser extent, with the white feminist movement